Modified Adenovirus Prime-Protein Boost Clade C HIV Vaccine Strategy Results in Reduced Viral DNA in Blood and Tissues Following Tier 2 SHIV Challenge - Malherbe, Delphine C.; Vang, Lo; Mendy, Jason; Barnette, Philip T.; Spencer, David A.; Reed, Jason; Kareko, Bettie W.; Sather, D. Noah; Pandey, Shilpi; Wibmer, Constantinos K.; Robins, Harlan; Fuller, Deborah H.; et al. (Frontiers in Immunology, 2021)
Designing immunogens and improving delivery methods eliciting protective immunity is a paramount goal of HIV vaccine development. A comparative vaccine challenge study was performed in rhesus macaques using clade C HIV Envelope (Env) and SIV Gag antigens. One group was vaccinated using co-immunization with DNA Gag and Env expression plasmids and trimeric Env gp140 glycoprotein (DNA+Protein), and the other using a prime-boost approach composed of replicating simian (SAd7) adenovirus-vectored vaccines paired with the same gp140 trimer (SAd7+Protein). The env genes were isolated from a pre-peak neutralization timepoint approximately one year post infection in CAP257, an individual with a high degree of neutralization breadth. These envs were selected based on immunogenicity studies in rabbits and nonhuman primates. Both DNA+Protein and SAd7+Protein vaccine strategies elicited significant Env-specific T cell responses, lesser Gag-specific responses, and moderate frequencies of Env-specific TFH cells. Both vaccine modalities readily elicited systemic and mucosal Env-specific IgG. There was a higher frequency and magnitude of ADCC activity in the SAd7+Protein than the DNA+Protein arm. All macaques developed moderate Tier 1 heterologous neutralizing antibodies, while neutralization of Tier 1B or Tier 2 viruses was sporadic and found primarily in macaques in the SAd7+Protein group at the time of challenge. Neither vaccine approach provided significant protection from viral acquisition against repeated titered mucosal challenges with a heterologous Tier 2 clade C SHIV, consistent with failure to neutralize this virus in vitro. However, lymphoid and gut tissues collected at necropsy and assessed individually for copies of viral DNA showed that animals in both vaccine groups each had significantly lower viral DNA compared to levels in controls. In the SAd7+Protein-vaccinated macaques, total and peak PBMC viral DNA were significantly lower compared with controls. Taken together, this heterologous Tier 2 SHIV challenge study shows that combination vaccination with SAd7+Protein was superior to combination DNA+Protein in reducing viral seeding in tissues in the absence of protection from infection, thus emphasizing the priming role of replication-competent SAd7 vector. Despite the absence of correlates of protection, because antibody responses were significantly higher in this vaccine group, we hypothesize that vaccine-elicited antibodies contribute to limiting tissue viral seeding.